Musical instruments, oral problems and prosthodontics: A review and a clinical report of a musician menopausal woman - Spyridon Stefos (Journal of Dental Problems and Solutions - Peertechz Publications, 2023)
The condition of teeth and the function of the oral organs are important when playing musical, especially brass or wind, instruments. This article describes the prosthodontic treatment provided for a musician who had lost a tooth and her subsequent musical performance. The relevant literature is also discussed. A 49-year-old professional clarinet player who fractured and avulsed the upper left central incisor during a fall sought maxillofacial rehabilitation for the missing tooth to maintain her ability to play the clarinet. Her treatment consisted of a provisional removable prosthesis with an acrylic base and clasps followed by a final fixed implant and conventional prostheses, designed accordingly. Her satisfaction with the prostheses was assessed by a self-reported questionnaire. The dental treatment helps to ensure that the musicians with oral, mainly prosthodontic, problems can continue playing the wind or brass instrument, especially the clarinet at their previous performance level professionally.